2015
DOI: 10.1039/c4ra12071j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alkyl substituents in BODIPYs: a comparative DFT computational investigation

Abstract: A detailed computational investigation encompassing the effects of alkyl groups in the structural and electronic properties of BODIPY dyes is presented. Abstract:Random changes in the alkyl substitution patterns in fluorescent dyes e.g. BODIPYs often accompany with significant changes in their photophysical properties. To understand such alteration of properties in closely related molecular systems, a comparative DFT (density functional theory) computational investigation was performed in order to comprehend t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 67 publications
2
35
0
Order By: Relevance
“…Mukherjee and Thilagar investigated substitutions around the BODIPY core with respect to relative stability of the electronic ground states. 46 They found that alkyl substitutions at the 3/5-positions contributed to a stabilization of the ground-state energy coupled with planar relaxed S0 geometries.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…Mukherjee and Thilagar investigated substitutions around the BODIPY core with respect to relative stability of the electronic ground states. 46 They found that alkyl substitutions at the 3/5-positions contributed to a stabilization of the ground-state energy coupled with planar relaxed S0 geometries.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…6,9,10 Substituted BOD-IPY molecules are of considerable interest since the observed photophysical properties are highly sensitive to the nature of the substitution, and there have been several recent computational studies concerned with the calculation of the absorption and emission properties of BODIPY based systems. [11][12][13][14][15][16] These include the incorporation of solvent via a polarised continuum model. 12,15 In this work we focus on a triazacryptand-based fluorescent sensor with a 4-amino-naphthalimide fluorophore reported by Zhou et.…”
Section: Introductionmentioning
confidence: 99%
“…Calculations of electronic absorption spectra were done with the TD‐DFT method at the B3LYP/6‐31G(d) level on the basis of the optimized ground‐state structures. As this method has been widely used and given reliable results in the past reports . The results were given in Table .…”
Section: Discussionmentioning
confidence: 99%